Enzymatic cleavage specificity of the proα1(V) chain processing analysed by site-directed mutagenesis - Bonod-Bidaud, Christelle (Portland Press Ltd., 2007)
The proteolytic processing of procollagen V is complex and depends on the activity of several enzymes among which the BMP-1 (bone morphogenetic protein-1)/tolloid metalloproteinase and the furin-like proprotein convertases. Few of these processing interactions could have been predicted by analysing the presence of conserved consensus sequences in the proα1(V) chain. In the present study we opted for a cell approach that allows a straightforward identification of processing interactions. A construct encompassing the complete N-terminal end of the proα1(V) chain, referred to as Nα1, was recombinantly expressed to be used for enzymatic assays and for antibody production. Structural analysis showed that Nα1 is a monomer composed of a compact globule and an extended tail, which correspond respectively to the non-collagenous Nα1 subdomains, TSPN-1 (thrombospondin-1 N-terminal domain-like) and the variable region. Nα1 was efficiently cleaved by BMP-1 indicating that the triple helix is not required for enzyme activity. By mutating residues flanking the cleavage site, we showed that the aspartate residue at position P2′ is essential for BMP-1 activity. BMP-1 activity at the C-terminal end of the procollagen V was assessed by generating a furin double mutant (R1584A/R1585A). We showed that, in absence of furin activity, BMP-1 is capable of processing the C-propeptide even though less efficiently than furin. Altogether, our results provide new relevant information on this complex and poorly understood mechanism of enzymatic processing in procollagen V function.